Foot and mouth disease virus transmission among vaccinated pigs after exposure to virus shedding pigs - Orsel, K.; de Jong, M.C.M.; Bouma, A.; Stegeman, J.A.; Dekker, A. (Vaccine, 2007)
The aim of this study was to design a transmission experiment that enabled quantification of the effectiveness of vaccination against foot and mouth disease (FMD) virus in groups of pigs. Previous experiments showed that intradermal injection of pigs with FMD virus 14 days after vaccination was not suitable to start an infection chain, as inoculated vaccinated pigs resisted challenge. Therefore, we carried out two experiments in which we used direct contact to a non-vaccinated pig as route of infection. In the first experiment only the vaccine effect on susceptibility was quantified by exposing pigs, either vaccinated 14 days before or not vaccinated, each to a non-vaccinated seeder pig inoculated with FMD virus O/NET/2001. Since no significant differences were observed between contact infections in vaccinated or non-vaccinated pigs, we performed a second experiment in which both susceptibility and infectivity were subject to vaccination. We quantified virus transmission in homogenous groups of vaccinated or non-vaccinated pigs in which the infection chain was started by exposure to a third group of non-vaccinated infected pigs. Transmission occurred to all contact-exposed pigs in the non-vaccinated groups and to 9 out of 10 contact-exposed pigs in the vaccinated groups. The rate of transmission ( β) was significantly reduced in the vaccine group. Yet, the estimated reproduction ratio in both groups was still above 1. In conclusion, by adjusting our transmission study design and challenge method, we were able to quantify transmission of FMDV among vaccinated pigs. According to this study a single vaccination was not sufficient to stop pig to pig virus transmission. With these results major outbreaks may still be expected, even in groups of vaccinated pigs.